DISTRIBUTION OF SETTLEMENT PATTERNS AND CHARACTERISTICS OF SOCIOECONOMIC IN LINGKUANG AUA VILLAGE PASAMAN DISTRICT OF PASAMAN BARAT REGION - SEPTIAN, NANDA; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Despica, S.Pd., M.Si, Rika (STKIP PGRI Sumbar, 2014)
ABSTRACT This study aims to determine the pattern of settlement and Socioeconomic Characteristics in Lingkuang Aua Village Pasaman District of Pasaman Barat Region.This research is descriptive quantitative. The population in this study were all Head of Family in Lingkuang Aua Village Pasaman District of Pasaman Barat Region totaling 7.770 households. Samples were taken in two ways, sample areas taken by using purposive side which is ellipse with a radius of 2,5 miles from Pasaman Barat Region Head Office and the sample respondents drawn with proportional random sampling technique with percentage 5% so that the sample was 170 households. Data were analyzed by analysis of nearest neighbors and the percentage.The results of the study found that: (1) settlement pattern in Lingkuang Aua Village Pasaman District are clustered settlement pattern and (2) socio-economic characteristics of society in Lingkuang Aua Village Pasaman District, community family structure more female population than the male, with the age group most are in the productive age. Family child education generally is at the level of elementary, junior high, high school and college, but there are still children who drop out of school. Generally place a childs education in the neighborhood, the cost incurred an average of Rp 300,000 - Rp 500.000/ month than the cost of its own, without any help from others, average income of Rp 1,000,000 - Rp 2.000.000/month, spending on basic necessities average < Rp 1.500.000/month, to meet the needs of food, clothing and shelter, dependents in a family of 4 people and has no dependents other than son and wife. The main livelihood in agriculture, employment status remain and work in the city district. Are by and large people do not have a second job